2017
DOI: 10.1042/bsr20170095
|View full text |Cite
|
Sign up to set email alerts
|

Associations between male reproductive characteristics and the outcome of assisted reproductive technology (ART)

Abstract: The present study was designed to investigate the relationships between indicators of male body mass index (BMI), age, reproductive hormone levels, semen parameters, and the outcomes of assisted reproductive technology (ART). The clinical data were collected from 636 couples who underwent ART between January, 2013 and December, 2015 at the reproductive center involved in our study. Pearson's correlation or Spearman rank correlation was applied to establish the relevant correlation coefficients. The correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
(39 reference statements)
2
7
1
Order By: Relevance
“…Meanwhile, there was a significant difference in the male age between the 2 groups in the current study, but the age of the males in the 2 groups was not old enough to affect ART outcome (male age >50) (26). Also, male FSH, LH, and testicular volume did not effect ART outcome (27), despite significant differences between the 2 groups. In addition, the 2 groups differed significantly in the rate of ICSI cycles with fresh sperm (P< .05), affecting neither the CCPR nor the cumulative LBDR by logistic regression (CCPR, P¼ .746; cumulative LBDR, P¼ .296; data not shown).…”
Section: Discussioncontrasting
confidence: 56%
“…Meanwhile, there was a significant difference in the male age between the 2 groups in the current study, but the age of the males in the 2 groups was not old enough to affect ART outcome (male age >50) (26). Also, male FSH, LH, and testicular volume did not effect ART outcome (27), despite significant differences between the 2 groups. In addition, the 2 groups differed significantly in the rate of ICSI cycles with fresh sperm (P< .05), affecting neither the CCPR nor the cumulative LBDR by logistic regression (CCPR, P¼ .746; cumulative LBDR, P¼ .296; data not shown).…”
Section: Discussioncontrasting
confidence: 56%
“…As for clinical outcomes between severe oligozoospermia and mild oligozoospermia, several studies have concluded that sperm concentration positively affects the likelihood of achieving pregnancy. 27 28 29 However, our results agree with the findings of Zheng et al . 13 whereby decreased sperm concentration and motility retarded ICSI fertilization rates; however, no differences in live birth rates were observed.…”
Section: Discussionsupporting
confidence: 92%
“…The logistic regression analysis of cumulative live births demonstrated that female age and BMI were negatively associated with cumulative live birth, which is consistent with earlier studies. 29 31 Interestingly, our results also demonstrated that male age is positively associated with birth outcome. Only a few studies have investigated this association, specifically that male age has a positive impact on fertility outcomes.…”
Section: Discussionsupporting
confidence: 72%
“…These evidences are in support of our findings, suggesting a critical role of LH in sperm motility. Although recent studies support that LH may be also implicated in sperm morphology [24,25], specific mechanisms remain unknown. More functional research is warranted to clarify the current results.…”
Section: Discussionmentioning
confidence: 99%